2021
DOI: 10.3390/f12060657
|View full text |Cite
|
Sign up to set email alerts
|

Plantations of Cinnamomum camphora (Linn) Presl with Distinct Soil Bacterial Communities Mitigate Soil Acidity within Polluted Locations in Southwest China

Abstract: Although the underlying mechanisms remain unknown, soils from different forest types exhibit distinct acidification-buffering capacities. We investigated soil properties and bacterial communities across five plantation types and different soil horizons in a severely acid-polluted site in Southwest China and evaluated the potential mechanisms driving differences in community structure. Soils collected from pure stands of Pinus massoniana Lamb.or Schima superba Gardn. et Champ. or mixed stands of these species s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Our data showed that throughfall N input was negatively associated with soil pH, which is supported by a study from an urban-to-rural transect in southern China [ 55 ]. In this study, throughfall NO 3 − flux was the highest in Pi stands, and the lowest in Ci stands, where lower N input of throughfall (plus stemflow) and litter leachate contributed to higher pH values of the soils, an observation supported by our previous data as well [ 10 ].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our data showed that throughfall N input was negatively associated with soil pH, which is supported by a study from an urban-to-rural transect in southern China [ 55 ]. In this study, throughfall NO 3 − flux was the highest in Pi stands, and the lowest in Ci stands, where lower N input of throughfall (plus stemflow) and litter leachate contributed to higher pH values of the soils, an observation supported by our previous data as well [ 10 ].…”
Section: Discussionsupporting
confidence: 89%
“…The study site in Han et al [ 27 ] was located in northwest China, which does not experience acid rain or soil acidification [ 53 ]. Our study was conducted in a typical acid-polluted area with severely acidic soil (average pH of 3.98, 4.54, and 4.6, respectively, in O_horizon of Pi, Pi_Ci and Ci, [ 10 ]), which would benefit from species that could supply less acidic rain water and greater base saturation. We also calculated the base saturation of throughfall, stemflow, and litter leachate, finding that Ci had the highest base saturation, followed by Pi_Ci ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations